Old Armenian (Grabar) as a Source of Developing Terms in Modern Eastern Armenian Vocabulary - Mikayelyan, Karine (Bulletin of Yerevan University B: Philology, 2024)
In the result of the research carried out on the changes in the semantic fields of terms which have passed from Grabar to Eastern Armenian vocabulary, in the present article the following conclusions have been drawn: firstly, the process of creating terms in Armenian could be observed not only in the pre-Grabar, but also in the post-Grabar periods. Secondly, in Grabar creating of terms was carried out through semantic transition or reinterpretation such as word in Grabar- into term in modern Armenian, term in Grabar into term in modern Armenian or word and term, both in Grabar and in modern Armenian. In modern Eastern Armenian, new created terms were added not only to the same, but also to the new and homonymous terminological exterior systems. The process of developing terminology in the national language needs great care, such as correct language policy, active participation of professionals, which is complicated and time consuming. Terminology in the mother tongue may produce differences between the scientific and applied languages creating difficulties in international cooperation and communication. Therefore, the development of the terminological system in the native language is of great importance for preserving culture, spreading knowledge and providing language autonomy, but there are still several challenges that call for balanced and strategic approach.